Investigation of Drugs’ Adsorption by the Perfluorane - N. N. Pshenkina; O. M Veselova; Ye. V. Murzina; G. A. Sofronov (Общая реаниматология, 2011)
Objective: to estimate the perfluorane adsorption capacity of the drugs belonging to different pharmacological groups. Materials and methods. The binding of perfluorane to 50 drugs at concentrations of 12.5 to 100 ^M was studied in vitro using equilibrium dialysis. Results. Interactions of ligands with the particles of perfluorane emulsion were found to be of three types. Type 1 substances were characterized by negative affinity to perfluorane; type 2 ligands acted indifferently with the emulsion; type 3 compounds were reversibly adsorbed with the particles of the blood substitute by the affinity constants ( Kaff) of 104 M-1. Conclusion. The perfluorane adsorption capacity is ambiguous and seems to depend on the properties of ligands. Type 3 interactions, which may lead to an increase in blood adsorption capacity and change in the pharmacokinet-ics of drugs used in combination with perfluorane, appear to be the most important. Key words: perfluorane, binding, drugs, drug interactions.